Do better schools lead to more growth?: cognitive skills, economic outcomes, and causation - Eric Alan Hanushek; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2009)
We provide evidence that the robust association between cognitive skills and economic growth reflects a causal effect of cognitive skills and supports the economic benefits of effective school policy. We develop a new common metric that allows tracking student achievement across countries, over time, and along the within-country distribution. Extensive sensitivity analyses of cross-country growth regressions generate remarkably stable results across specifications, time periods, and country samples. In addressing causality, we find, first, significant growth effects of cognitive skills when instrumented by institutional features of school systems. Second, home-country cognitive-skill levels strongly affect the earnings of immigrants on the U.S. labor market in a difference-in-differences model that compares home-educated to U.S.-educated immigrants from the same country of origin. Third, countries that improved their cognitive skills over time experienced relative increases in their growth paths. From a policy perspective, the shares of basic literates and high performers have independent significant effects on growth that are complementary to each other, and the high-performer effect is larger in poorer countries.
Keywords: O4; I2; 330; Bildungsniveau; Kognition; Wirtschaftswachstum; Bildungsökonomik; Kausalanalyse; Welt; Migranten; Bildungsertrag; USA